Perancangan Sistem Informasi Peminjaman dan Pengembalian Berkas Rekam Medis Rawat Jalan dengan Metode Waterfall - Arta, I Gusti; sutha, diah; Ali, Amir; Putra, Yunior Bimasekti (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
Wiyung Sejahtera Hospital in recording the borrowing and returning of outpatient medical records still uses expedition books which are recorded manually. The research aims to design and develop an information system to facilitate the process of borrowing and returning outpatient medical record files using the Waterfall method approach. The Waterfall method was chosen because of its ability to divide system development into structured stages, starting from requirements analysis to maintenance. The needs analysis stage involves an in-depth study of existing processes and user needs. Next, system design is carried out by building a design plan that includes database structure, user interface design, and system workflow. System implementation is carried out by developing applications based on previous designs, while system testing is carried out thoroughly to ensure quality and performance before full implementation. The maintenance stage is carried out to ensure system operation and carry out continuous repairs and improvements. As a result, it is hoped that this system can improve the efficiency and quality of outpatient medical record file management and health services as a whole. The conclusion of this research is the successful design and development of a computer-based information system for borrowing and returning outpatient medical records at Wiyung Sejahtera Hospital using the waterfall method.